Recent advances in understanding and mitigating adipogenic and metabolic effects of antipsychotic drugs - Gohlke, Julia M.; Dhurandhar, Emily J.; Correll, Christoph U.; Morrato, Elaine H.; Newcomer, John W.; Remington, Gary; Nasrallah, Henry A.; Crystal, Stephen; Nicol, Ginger; Allison, David B. (Frontiers in Psychiatry, 2012)
Although offering many benefits for several psychiatric disorders, antipsychotic drugs (APDs) as a class have a major liability in their tendency to promote adiposity, obesity, and metabolic dysregulation in an already metabolically vulnerable population. The past decade has witnessed substantial research aimed at investigating the mechanisms of these adverse effects and mitigating them. On July 11 and 12, 2011, with support from 2 NIH institutes, leading experts convened to discuss current research findings and to consider future research strategies. Five areas where significant advances are being made emerged from the conference: (1) methodological issues in the study of APD effects; (2) unique characteristics and needs of pediatric patients; (3) genetic components underlying susceptibility to APD-induced metabolic effects; (4) APD effects on weight gain and adiposity in relation to their acute effects on glucose regulation and diabetes risk; and (5) the utility of behavioral, dietary, and pharmacological interventions in mitigating APD-induced metabolic side effects. This paper summarizes the major conclusions and important supporting data from the meeting.